The Effect Of Creative Problem Solving Model On The Creative Thingking Skill Of Student At Smp Negeri 29 Padang - Fitri, Nurmiati; Arif, Khairil; Lestari, Tuti; Yanto, Febri (SEMESTA: Journal of Science Education and Teaching, 2025)
This study aims to determine the effect of the Creative Problem-Solving (CPS) learning model on the creative thinking skills of eighth-grade students at SMP Negeri 29 Padang. The research employed a quasi-experimental design with a nonequivalent control group. The study was conducted at SMP Negeri 29 Padang, West Sumatra. The sample was selected using purposive sampling, consisting of 34 students from class VIII-9 as the experimental group and 34 students from class VIII-6 as the control group. The instrument used was a test in the form of essay questions. The results showed that the hypothesis was accepted, as the significance value obtained was less than 0.05. These findings suggest that the implementation of the Creative Problem-Solving learning model is an effective strategy for enhancing students’ creative thinking skills. Therefore, it is recommended that teachers integrate the CPS model into classroom instruction to encourage students to be more active, innovative, and capable of solving problems creatively.